2020
DOI: 10.1016/j.drugalcdep.2020.108257
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, preparedness, and compassion fatigue among law enforcement officers who respond to opioid overdose

Abstract: Highlights Most patrol officers who respond to OD calls receive training and carry naloxone. One in three officers report making an arrest at an OD scene in the past 6 months. A minority of officers correctly described their state’s Good Samaritan Law. Officer endorsement of OD-prevention strategies decreases as OD response increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…Another approach involves reshaping police officers’ knowledge, attitudes and beliefs [ 16 ]. Educating police has proven critical to the success of local syringe service programs [ 5 , 53 , 59 ] and Good Samaritan laws [ 9 ]. However, some studies found that evidence-based training can exacerbate younger officers’ negative attitudes towards PWUD [ 62 ] and harm reduction training for police should account for gender differences in behavior; male officers were found to be more likely to confiscate syringes from PWUD than female officers [ 37 , 46 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another approach involves reshaping police officers’ knowledge, attitudes and beliefs [ 16 ]. Educating police has proven critical to the success of local syringe service programs [ 5 , 53 , 59 ] and Good Samaritan laws [ 9 ]. However, some studies found that evidence-based training can exacerbate younger officers’ negative attitudes towards PWUD [ 62 ] and harm reduction training for police should account for gender differences in behavior; male officers were found to be more likely to confiscate syringes from PWUD than female officers [ 37 , 46 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overtime, through numerous planning meetings, emails, phone calls, and visits to the hotel bar between conference sessions with various ORS collaborators, I became familiar with some of the many strategies law enforcement professionals can engage to produce knowledge of and continuously validate their epistemic authority over the illicit drug market. Hardly systematic, my insights about the cultures, strategies, and discourses of law enforcement institutions emerged organically though the repetitive motions of my professional duties as a public health consultant: explaining public health to law enforcement; explaining law enforcement to public health; and explaining my research about law enforcement (Carroll, Mital, et al, 2020) back to law enforcement to facilitate meaningful public health partnerships. I refined my understanding of my interlocutors’ conceptual schemas and modeled worlds every step of the way.…”
Section: Methods and Messmentioning
confidence: 99%
“…Indeed, one recent study found that in a national sample of police officers who respond to overdose, more than one-third (36%) reported making an arrest at an overdose scene (11), suggesting that enforcement does occur during overdose response. The potential for arrest at overdose scenes and subsequent druginduced homicide prosecutions remains an important consideration for health officials as reliance on police as overdose first responders becomes standard in many jurisdictions through police equipment with naloxone.…”
Section: An Important Distinctionmentioning
confidence: 99%